Singing from the same song sheet? Exploring "civil society" through the eyes of NGO practitioners. Issue 8 (16th November 2020) - Thomas, Sarah
ABSTRACT: Although historically a contested concept, it has been argued that civil society has become a victim of its own ubiquity in development; its potential for radicalism and innovation blunted by donor-driven narratives and the unquestioning acceptance of those narratives by donor-dependent NGOs. Donor influence is charged with weakening civil society as an arena for political debate and citizen-driven change. This article presents findings from qualitative research undertaken with forest sector civil society organisations in the Central African Republic. It unearths and examines perceptions of the roles and values of civil society among practitioners themselves and the underlying drivers of consensual or contested understandings.